32‐4: In‐situ Polymerization of Polystyrene for Synthesis of Quantum Dots Composite Particle for Wide Color Gamut Display. Issue 1 (2nd June 2017) - Yang, Lei; Liu, Haochen; Lu, Rui; Chen, Wei; Hao, Junjie; An, Na; Ma, Haoyue; Wu, Dan; Bian, Dun; Wang, Kai
Abstract : CdSe/ZnS quantum dots with multi‐shell structure had been synthesized and employed in polymer particle fabrication by an in‐situ polymerization method. The composites with red and green emission had been utilized in on‐chip packaging of display light emitting diodes, reaching a 110% NTSC for display color gamut.